Characterization of Liquid Skim Milk Fortified with Whey-Mangosteen Pericarp (Garcinia mangostana) Extract Solution - Jaya Mahar Maligan; Mahsa Ridhani Jordan; Ria Dewi Andriani; Premy Puspitawati Rahayu; Teti Estiasih (Engineering Faculty, University of Pembangunan Nasional Jawa Timur, 2020)
Mangosteen pericarp has many health benefits. The types of mangosteen-based functional foods and drinks are still very limited, because the phenolic components of the mangosteen pericarp extract are easily damaged and cannot be fully absorbed by the body. Whey protein in milk is believed to function as a carrier for food. This whey protein can form complexes with phenolic components and can improve its physical and functional properties. In producing functional foods that are more stable, whey complexes - extracts of mangosteen pericarps that have been formed are fortified into skim milk. Addition of whey-mangosteen pericarp extract solution not significantly affected (α= 0,05) to creaming, sedimentation, and solubility of skim milk. However, there was enlargement in particle size of each concentration. The best treatment in this study was the concentration of adding 5% whey-extract of mangosteen pericarp extract with a phase separation value of 7.33% ± 0.70, the value of solubility reached 92.90 ± 4.86, the sedimentation value reached 0.0211 ± 0.007 , and the average particle diameter was 3.9 µm